Skills Guidance of Residents in Institutions of Special Guidance for Class I Children in Palembang City - Ruhus, Norsyaidina; Nurrizalia, Mega; Shomedran, Shomedran (International Journal of Pedagogy and Learning Community (IJPLC), 2025)
The objective of this research is to investigate the development of skills among inmates at the Special Child Rehabilitation Institution (LPKA) Class I in Palembang City. The research methodology employed is qualitative descriptive approach. Data collection is conducted through interviews, observation, and documentation. The study involves four subjects, comprising two inmates, one institution supervisor, and one prison officer. The results indicate that personality skills are divided into three aspects: religious awareness development, which has been implemented and perceived by both inmates and other personnel. Hence, the effective collaboration of stakeholders at LPKA Class I in Palembang City is crucial. Intellectual development has been successfully executed through partnerships with schools in Palembang and adequate facilities for inmates to utilize during their detention. Legal awareness development is also progressing well and is supported by physical infrastructure, advice, and available facilities, albeit facing implementation challenges due to violations by some individuals. Life skills development is proceeding smoothly, with each inmate showcasing their unique talents. Consequently, LPKA Class I in Palembang City facilitates the distribution and advancement of these talents through activities held within the institution.